A Novel Pairwise Comparison-Based Method to Determine Radiation Dose Reduction Potentials of Iterative Reconstruction Algorithms, Exemplified Through Circle of Willis Computed Tomography Angiography - Ellmann, Stephan; Kammerer, Ferdinand; Brand, Michael; Allmendinger, Thomas; May, Matthias; Uder, Michael; Lell, Michael; Kramer, Manuel (Investigative Radiology, 2016)
The aim of this study was to determine the dose reduction potential of iterative reconstruction (IR) algorithms in computed tomography angiography (CTA) of the circle of Willis using a novel method of evaluating the quality of radiation dose-reduced images.This study relied on ReconCT, a proprietary reconstruction software that allows simulating CT scans acquired with reduced radiation dose based on the raw data of true scans. To evaluate the performance of ReconCT in this regard, a phantom study was performed to compare the image noise of true and simulated scans within simulated vessels of a head phantom. That followed, 10 patients scheduled for CTA of the circle of Willis were scanned according to our institute's standard protocol (100 kV, 145 reference mAs). Subsequently, CTA images of these patients were reconstructed as either a full-dose weighted filtered back projection or with radiation dose reductions down to 10% of the full-dose level and Sinogram-Affirmed Iterative Reconstruction (SAFIRE) with either strength 3 or 5. Images were marked with arrows pointing on vessels of different sizes, and image pairs were presented to observers. Five readers assessed image quality with 2-alternative forced choice comparisons.In the phantom study, no significant differences were observed between the noise levels of simulated and true scans in filtered back projection, SAFIRE 3, and SAFIRE 5 reconstructions.The dose reduction potential for patient scans showed a strong dependence on IR strength as well as on the size of the vessel of interest. Thus, the potential radiation dose reductions ranged from 84.4% for the evaluation of great vessels reconstructed with SAFIRE 5 to 40.9% for the evaluation of small vessels reconstructed with SAFIRE 3.This study provides a novel image quality evaluation method based on 2-alternative forced choice comparisons. In CTA of the circle of Willis, higher IR strengths and greater vessel sizes allowed higher degrees of radiation dose reduction.
EVALuna2:14492

Attenuation-based automatic kilovolt (kV)-selection in computedtomography of the chest: Effects on radiation exposure and imagequality - Eller, Achim; Wüst, Wolfgang; Scharf, Michael; Brand, Michael; Achenbach, Stephan; Uder, Michael; Lell, Michael (European Journal of Radiology, 2013)
Objectives: To evaluate an automated attenuation-based kV-selection in computed tomography of thechest in respect to radiation dose and image quality, compared to a standard 120 kV protocol.Materials and methods: 104 patients were examined using a 128-slice scanner. Fifty examinations (58 ± 15years, study group) were performed using the automated adaption of tube potential (100-140 kV), basedon the attenuation profile of the scout scan, 54 examinations (62 ± 14 years, control group) with fixed120 kV. Estimated CT dose index (CTDI) of the software-proposed setting was compared with a 120 kVprotocol. After the scan CTDI volume (CTDIvol) and dose length product (DLP) were recorded. Imagequality was assessed by region of interest (ROI) measurements, subjective image quality by two observerswith a 4-point scale (3 - excellent, 0 - not diagnostic).Results: The algorithm selected 100 kV in 78% and 120 kV in 22%. Overall CTDIvol reduction was 26.6%(34% in 100 kV) overall DLP reduction was 22.8% (32.1% in 100 kV) (all p < 0.001). Subjective image qualitywas excellent in both groups.Conclusion: The attenuation based kV-selection algorithm enables relevant dose reduction (?27%) inchest-CT while keeping image quality parameters at high levels. © 2013 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Chest; Computed tomography; Dose reduction; Tube potentialImage quality

Automated tube voltage adaptation in head and neck computed tomography between 120 and 100 kV: effects on image quality and radiation dose - May, Matthias; Kramer, Manuel; Eller, Achim; Wüst, Wolfgang; Scharf, Michael; Brand, Michael; Saake, Marc; Schmidt, Bernhard; Uder, Michael; Lell, Michael (Neuroradiology, 2014)
Low tube voltage allows for computed tomography (CT) imaging with increased iodine contrast at reduced radiation dose. We sought to evaluate the image quality and potential dose reduction using a combination of attenuation based tube current modulation (TCM) and automated tube voltage adaptation (TVA) between 100 and 120 kV in CT of the head and neck.One hundred thirty consecutive patients with indication for head and neck CT were examined with a 128-slice system capable of TCM and TVA. Reference protocol was set at 120 kV. Tube voltage was reduced to 100 kV whenever proposed by automated analysis of the localizer. An additional small scan aligned to the jaw was performed at a fixed 120 kV setting. Image quality was assessed by two radiologists on a standardized Likert-scale and measurements of signal- (SNR) and contrast-to-noise ratio (CNR). Radiation dose was assessed as CTDIvol.Diagnostic image quality was excellent in both groups and did not differ significantly (p = 0.34). Image noise in the 100 kV data was increased and SNR decreased (17.8/9.6) in the jugular veins and the sternocleidomastoid muscle when compared to 120 kV (SNR 24.4/10.3), but not in fatty tissue and air. However, CNR did not differ statistically significant between 100 (23.5/14.4/9.4) and 120 kV data (24.2/15.3/8.6) while radiation dose was decreased by 7-8%.TVA between 100 and 120 kV in combination with TCM led to a radiation dose reduction compared to TCM alone, while keeping CNR constant though maintaining diagnostic image quality.
EVALuna2:14375

Breast MRI at Very Short TE (minTE): Image Analysis of minTE Sequences on Non-Fat-Saturated, Subtracted T1-Weighted Images - Wenkel, Evelyn; Janka, Rolf Matthias; Geppert, Christian; Kämmerer, Nadine; Hartmann, Arndt; Uder, Michael; Hammon, Matthias; Brand, Michael (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose The aim was to evaluate a minimum echo time (minTE) protocol for breast magnetic resonance imaging (MRI) in patients with breast lesions compared to a standard TE (nTE) time protocol. Methods Breasts of 144 women were examined with a 1.5 Tesla MRI scanner. Additionally to the standard gradient-echo sequence with nTE (4.8 ms), a variant with minimum TE (1.2 ms) was used in an interleaved fashion which leads to a better temporal resolution and should reduce the scan time by approximately 50 %. Lesion sizes were measured and the signal-to-noise ratio (SNR) as well as the contrast-to-noise ratio (CNR) were calculated. Subjective confidence was evaluated using a 3-point scale before looking at the nTE sequences (1 = very sure that I can identify a lesion and classify it, 2 = quite sure that I can identify a lesion and classify it, 3 = definitely want to see nTE for final assessment) and the subjective image quality of all examinations was evaluated using a four-grade scale (1 = sharp, 2 = slight blur, 3 = moderate blur and 4 = severe blur/not evaluable) for lesion and skin sharpness. Lesion morphology and contrast enhancement were also evaluated. Results With minTE sequences, no lesion was rated with "definitely want to see nTE sequences for final assessment". The difference of the longitudinal and transverse diameter did not differ significantly (p > 0.05). With minTE, lesions and skin were rated to be significantly more blurry (p < 0.01 for lesions and p < 0.05 for skin). There was no difference between both sequences with respect to SNR, CNR, lesion morphology, contrast enhancement and detection of multifocal disease. Conclusion Dynamic breast MRI with a minTE protocol is feasible without a major loss of information (SNR, CNR, lesion morphology, contrast enhancement and lesion sizes) and the temporal resolution can be increased by a factor of 2 using minTE sequences. Key points · Increase of temporal resolution for a better in-flow curve.. · Dynamic breast MRI with a shorter TE time is possible without relevant loss of information.. · Possible decrease of the overall scan time.. Citation Format · Wenkel E, Janka R, Geppert C et al. Breast MRI at Very Short TE (minTE): Image Analysis of minTE Sequences on Non-Fat-Saturated, Subtracted T1-Weighted Images. Fortschr Röntgenstr 2017; 189: 137 - 145.
EVALuna2:6843

Carotid CTA at the Lowest Tube Voltage (70 kV) in Comparison with Automated Tube Voltage Adaption - Eller, A.; Wiesmüller, Marco; Wüst, Wolfgang; Heiß, Rafael; Kopp, Markus; Saake, Marc; Brand, Michael; Uder, Michael; May, Matthias (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: CTA is the imaging modality of choice in many institutions for the evaluation of the supraaortic vessels, but radiation exposure remains a matter of concern. Our aim was to evaluate a 70-kV protocol for CT angiography of the carotid arteries with respect to image quality and radiation exposure compared with automated tube voltage adaption. MATERIALS AND METHODS: A total of 90 consecutive patients were included in this prospective study and randomized to the study group (n = 45, 70 kV) or control group (n = 45, automated tube voltage adaptation). Volume CT dose indices and dose-length products were recorded in the examination protocol. Image quality was assessed as arterial vessel contrast, signal-to-noise ratio, contrast-to-noise ratio, and contrast-to-noise ratio in reference to the radiation dose. Subjective overall image-quality analysis, image-artifact analysis, and diagnostic evaluation were performed by 2 observers by using a 4-point Likert scale. RESULTS: Radiation exposure was significantly lower in the study group (volume CT dose index reduced by 22%, dose-length product reduction by 20%; each P < .001). Contrast (P = .15), SNR (P = .4), and contrast-to-noise ratio (P = .5) did not show significant differences between the groups. The contrast-to-noise ratio in reference to the radiation dose was not significantly increased using the study protocol (P = .2). Subjective image quality and visualization of pathologic findings did not differ significantly between the groups. CONCLUSIONS: Carotid CTA using the lowest available voltage (70 kV) is feasible at very-low-dose levels, while overall image quality is comparable with protocols using automated tube voltage selection.
CRIS-Team Scopus Importer:2019-09-03

Chemoprevention of Radiation-Induced DNA Double-Strand Breaks with Antioxidants - Kuefner, Michael Andreas; Brand, Michael; Andreassi, Maria Grazia; Braga, Larissa; Uder, Michael (Current Radiology Reports, 2015)
Double-strand breaks (DSB) are considered to be the most relevant X-ray-induced DNA damages. γ-H2AX immunofluorescence microscopy is a sensitive and reliable method for the quantification of distinct DSB. The detectable amount of these DNA damages correlates well with the dose received. A protective effect of different antioxidants has been postulated. This review explains the principle of the γ-H2AX technique, describes important results concerning DSB in radiologic examinations, and provides an overview on studies evaluating the effect of antioxidants on radiation-induced DNA damages with a special focus on recent studies using the γ-H2AX method.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Antioxidants; Chemoprevention; DNA double-strand breaks; Radiation; γ-H2AX

Clinical outcome of patients with orbital fractures treated with patient specific CAD/CAM ceramic implants – A retrospective study - Falkhausen, Runa; Mitsimponas, Konstantinos; Adler, Werner; Brand, Michael; von Wilmowsky, Cornelius (Journal of Cranio-Maxillofacial Surgery, 2021)
The aim of this study was to determine whether patients benefit from a secondary reconstruction since it carries the risks of no improvement or worsening of their current situation. Patients treated with individual computer-aided-design/computer-aided-manufacturing (CAD/CAM) ceramic implants were reviewed. To ascertain changes throughout the secondary reconstruction, the study investigators reviewed ophthalmological examinations, took volumetric measurements of the orbits and asked the patients for evaluation of their situation before and after the reconstruction. Points addressed were double vision, visual acuity, field of vision, limitations in daily life and aesthetic considerations. A total of 14 patients were reviewed and 11 answered the questionnaire. Ophthalmological examinations showed that the physical integrity of the eye was maintained. Volumetric measurements preopeatively (33.94 ± 3.24 cm3) and postoperatively (30.67 ± 2.07 cm3) showed that a statistically significant overcorrection of orbital volume leads to good functional and aesthetic outcomes. Patients’ subjective opinions were that they greatly benefitted, especially concerning limitations in daily life, which improved by 4.4 ± 2.8 points out of 10 possible points, and aesthetics, with an improvement of 5.9 ± 1.78 points. Based on these findings, we conclude that secondary reconstructions contribute to improvement of the patients’ quality of life and therefore should be considered as an option to improve patients’ condition.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Clinical outcome; Patient reported outcome; Patient specific implant; Secondary orbital reconstruction

Comparison of dual- and single-source dual-energy CT in head and neck imaging - May, Matthias; Wiesmüller, Marco; Heiß, Rafael; Brand, Michael; Brügel, Joscha; Uder, Michael; Wüst, Wolfgang (European Radiology, 2019)
Objectives: The aim of this study was to compare image quality of single-source dual-energy CT (SS-DECT) with third-generation dual-source dual-energy CT (DS-DECT) in head and neck cancer. Materials and methods: One hundred two patients with histologically proven head and neck cancer were prospectively randomized to undergo radiation dose-matched SS-DECT (n = 51, 120 kV, split-filter technique, 384 ref. mAs) or DS-DECT (n = 51, 80/Sn150 kV, tube A 100/tube B 67 ref. mAs). Inline default images (DI) and virtual monoenergetic images (VMI) for two different low energies (40 and 60 keV) were reconstructed. Objective image quality was evaluated as dose-normalized contrast to noise ratio (CNRD), and subjective image quality was rated on a 5-point Likert scale. Results: In both groups, highest CNRD values for vessel and tumor attenuation were obtained at 40 keV. DS-DECT was significantly better than SS-DECT regarding vessel and tumor attenuation. Overall subjective image quality in the SS-DECT group was highest on the DI followed by 40 keV and 60 keV. In the DS-DECT group, subjective image quality was highest at 40 keV followed by 60 keV and the DI. Forty kiloelectron volts and 60 keV were significantly better in the DS-DECT compared to the SS-DECT group (both p < 0.01). Conclusions: In split-filter SS-DECT as well as in DS-DECT, highest overall image quality in head and neck imaging can be obtained with a combination of DI and low keV reconstructions. DS-DECT is superior to split-filter SS-DECT in terms of subjective image quality and vessel and tumor attenuation. Key Points: • Image quality was diagnostic with both dual-energy techniques; however, the dual-source technique delivered significantly better results. • Highest overall image quality in head and neck imaging can be obtained with a combination of default images and low keV reconstructions with both dual-energy techniques. • The results of this study may have relevance for the decision-making process regarding replacement of CT scanners and focused patient examination considering image quality and subsequent therapeutic decision-making.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Diagnostic imaging; Head and neck neoplasms; Image enhancement

Computed Tomography of the Head and Neck Region for Tumor Staging-Comparison of Dual-Source, Dual-Energy and Low-Kilovolt, Single-Energy Acquisitions - May, Matthias; Brügel, Joscha; Brand, Michael; Wiesmüller, Marco; Krauss, Bernhard; Allmendinger, Thomas; Uder, Michael; Wüst, Wolfgang (Investigative Radiology, 2017)
The aim of this study was to intra-individually compare the image quality obtained by dual-source, dual-energy (DSDE) computed tomography (CT) examinations and different virtual monoenergetic reconstructions to a low single-energy (SE) scan.Third-generation DSDE-CT was performed in 49 patients with histologically proven malignant disease of the head and neck region. Weighted average images (WAIs) and virtual monoenergetic images (VMIs) for low (40 and 60 keV) and high (120 and 190 keV) energies were reconstructed. A second scan aligned to the jaw, covering the oral cavity, was performed for every patient to reduce artifacts caused by dental hardware using a SE-CT protocol with 70-kV tube voltages and matching radiation dose settings. Objective image quality was evaluated by calculating contrast-to-noise ratios. Subjective image quality was evaluated by experienced radiologists.Highest contrast-to-noise ratios for vessel and tumor attenuation were obtained in 40-keV VMI (all P < 0.05). Comparable objective results were found in 60-keV VMI, WAI, and the 70-kV SE examinations. Overall subjective image quality was also highest for 40-keV, but differences to 60-keV VMI, WAI, and 70-kV SE were nonsignificant (all P > 0.05). High kiloelectron volt VMIs reduce metal artifacts with only limited diagnostic impact because of insufficiency in case of severe dental hardware. CTDIvol did not differ significantly between both examination protocols (DSDE: 18.6 mGy; 70-kV SE: 19.4 mGy; P = 0.10).High overall image quality for tumor delineation in head and neck imaging were obtained with 40-keV VMI. However, 70-kV SE examinations are an alternative and modified projections aligned to the jaw are recommended in case of severe artifacts caused by dental hardware.
EVALuna2:14672

Dissimilar DNA Damage to Blood Lymphocytes After 177Lu-Labeled DOTATOC or Prostate-Specific Membrane Antigen Therapy - Ritt, Philipp; Jobic, Camille; Beck, Michael; Schmidkonz, Christian; Kuwert, Torsten; Uder, Michael; Brand, Michael (Journal of Nuclear Medicine, 2021)
DNA double-strand breaks in cells of radionuclide-treated patients are quantifiable by immunofluorescence microscopy, using phosphorylation of histone-variant H2AX (γ-H2AX) to mark radiation-induced foci (RIFs). Using this method, we compared excess RIFs side by side in recipients of 177Lu-DOTATOC or 177Lu-prostate specific membrane antigen-617 (PSMA) radioligands. We also examined relations between blood dose and dose rate, RIFs, and platelet counts. Methods: Venous blood samples were obtained from 48 patients subjected to 177Lu-labeled radioligand therapy (177Lu-DOTATOC, 26; 177Lu-PSMA, 22) to quantify blood lymphocyte RIFs and blood activity concentrations at various time points, including baseline (before injection) and postinjection readings (5 min, 30 min, 4 h, 24 h, 48 h, and 72 h). Absorbed doses and dose rates to blood were derived from sequentially assessed blood activity concentrations and γ-camera imaging. Platelet levels in routine blood tests were monitored for 3 d after injection to assess responses. Results: RIF counts averaged 0.25 ± 0.15 at baseline. Postinjection RIF counts were significantly higher than baseline values, peaking at 5 min (average, 3.93 ± 2.51 min) and declining thereafter. Compared with RIF counts of 177Lu-DOTATOC, those of 177Lu-PSMA were significantly higher at 5 min after injection and significantly lower at 72 h after injection. These differences could not be fully explained by blood doses and dose rates, which were significantly higher for 177Lu-PSMA than for 177Lu-DOTATOC treatment at every time point. RIF counts overall correlated with dose rates across all time points (Pearson r = 0.78; P < 0.01) and with absorbed dose until 4 h after injection only (Pearson r = 0.42; P < 0.01). Declines in platelet concentration correlated significantly with RIFs at 72 h after injection (Pearson r = -0.34; P < 0.05). Conclusion: Although values generated by the currently used blood dosimetry model correlated with RIF counts, the difference observed in 177Lu-DOTATOC and 177Lu-PSMA treatment groups was unexplained. Significantly more RIFs were found in 177Lu-DOTATOC recipients by comparison, despite lower dose rates and blood doses, exposing a potential limitation.
CRIS-Team Scopus Importer:2021-03-19
Keywords: 177Lu-labeled therapy; DOTATOC; PSMA; radiation-induced foci; γ-H2AX

Dose reduction potential of iterative reconstruction algorithms in neck CTA-a simulation study - Ellmann, Stephan; Kammerer, Ferdinand; Allmendinger, Thomas; Brand, Michael; Janka, Rolf Matthias; Hammon, Matthias; Lell, Michael M.; Uder, Michael; Kramer, Manuel (Dentomaxillofacial Radiology, 2016)
This study aimed to determine the degree of radiation dose reduction in neck CT angiography (CTA) achievable with Sinogram-affirmed iterative reconstruction (SAFIRE) algorithms.10 consecutive patients scheduled for neck CTA were included in this study. CTA images of the external carotid arteries either were reconstructed with filtered back projection (FBP) at full radiation dose level or underwent simulated dose reduction by proprietary reconstruction software. The dose-reduced images were reconstructed using either SAFIRE 3 or SAFIRE 5 and compared with full-dose FBP images in terms of vessel definition. 5 observers performed a total of 3000 pairwise comparisons.SAFIRE allowed substantial radiation dose reductions in neck CTA while maintaining vessel definition. The possible levels of radiation dose reduction ranged from approximately 34 to approximately 90% and depended on the SAFIRE algorithm strength and the size of the vessel of interest. In general, larger vessels permitted higher degrees of radiation dose reduction, especially with higher SAFIRE strength levels. With small vessels, the superiority of SAFIRE 5 over SAFIRE 3 was lost.Neck CTA can be performed with substantially less radiation dose when SAFIRE is applied. The exact degree of radiation dose reduction should be adapted to the clinical question, in particular to the smallest vessel needing excellent definition.
EVALuna2:14595

Dual-Energy Computed Tomography Angiography of the Head and Neck With Single-Source Computed Tomography: A New Technical (Split Filter) Approach for Bone Removal - Kämmerer, Nadine; Brand, Michael; Hammon, Matthias; May, Matthias; Wuest, Wolfgang; Krauss, Bernhard; Uder, Michael; Lell, Michael (Investigative Radiology, 2016)
Dual-energy computed tomographic angiography (DE-CTA) has been demonstrated to improve the visualization of the head and neck vessels. The aim of this study was to test the potential of split-filter single-source dual-energy CT to automatically remove bone from the final CTA data set.Dual-energy CTA was performed in 50 consecutive patients to evaluate the supra-aortic arteries, either to grade carotid artery stenosis or to rule out traumatic dissections. Dual-energy CTA was performed on a 128-slice single-source CT system equipped with a special filter array to separate the 120-kV spectrum into a high- and a low-energy spectrum for DE-based automated bone removal. Image quality of fully automated bone suppression and subsequent manual optimization was evaluated by 2 radiologists on maximum intensity projections using a 4-grade scoring system. The effect of image reconstruction with an iterative metal artifact reduction algorithm on DE postprocessing was tested using a 3-grade scoring system, and the time demand for each postprocessing step was measured.Two patients were excluded due to insufficient arterial contrast enhancement; in the remaining 48 patients, automated bone removal could be performed successfully. The addition of iterative metal artifact reduction algorithm improved image quality in 58.3% of the cases. After manual optimization, DE-CTA image quality was rated excellent in 7, good in 29, and moderate in 10 patients. Interobserver agreement was high (? = 0.85). Stenosis grading was not influenced using DE-CTA with bone removal as compared with the original CTA. The time demand for DE image reconstruction was significantly higher than for single-energy reconstruction (42.1 vs 20.9 seconds).Our results suggest that bone removal in DE-CTA of the head and neck vessels with a single-source CT is feasible and can be performed within acceptable time and moderate user interaction.
EVALuna2:14603

Imaging the Parasinus Region with a Third-Generation Dual-Source CT and the Effect of Tin Filtration on Image Quality and Radiation Dose - Lell, Michael; May, Matthias; Brand, Michael; Eller, A.; Buder, Thomas; Hofmann, Eva Maria; Uder, Michael; Wüst, Wolfgang (American Journal of Neuroradiology, 2015)
CT is the imaging technique of choice in the evaluation of midface trauma or inflammatory disease. We performed a systematic evaluation of scan protocols to optimize image quality and radiation exposure on third-generation dual-source CT.CT protocols with different tube voltage (70-150 kV), current (25-300 reference mAs), prefiltration, pitch value, and rotation time were systematically evaluated. All images were reconstructed with iterative reconstruction (Advanced Modeled Iterative Reconstruction, level 2). To individually compare results with otherwise identical factors, we obtained all scans on a frozen human head. Conebeam CT was performed for image quality and dose comparison with multidetector row CT. Delineation of important anatomic structures and incidental pathologic conditions in the cadaver head was evaluated.One hundred kilovolts with tin prefiltration demonstrated the best compromise between dose and image quality. The most dose-effective combination for trauma imaging was Sn100 kV/250 mAs (volume CT dose index, 2.02 mGy), and for preoperative sinus surgery planning, Sn100 kV/150 mAs (volume CT dose index, 1.22 mGy). "Sn" indicates an additional prefiltration of the x-ray beam with a tin filter to constrict the energy spectrum. Exclusion of sinonasal disease was possible with even a lower dose by using Sn100 kV/25 mAs (volume CT dose index, 0.2 mGy).High image quality at very low dose levels can be achieved by using a Sn100-kV protocol with iterative reconstruction. The effective dose is comparable with that of conventional radiography, and the high image quality at even lower radiation exposure favors multidetector row CT over conebeam CT.
EVALuna2:14481

Improved Image Quality in Head and Neck CT Using a 3D Iterative Approach to Reduce Metal Artifact - Wüst, Wolfgang; May, Matthias; Brand, Michael; Bayerl, N.; Krauss, A.; Uder, Michael; Lell, Michael (American Journal of Neuroradiology, 2015)
Metal artifacts from dental fillings and other devices degrade image quality and may compromise the detection and evaluation of lesions in the oral cavity and oropharynx by CT. The aim of this study was to evaluate the effect of iterative metal artifact reduction on CT of the oral cavity and oropharynx.Data from 50 consecutive patients with metal artifacts from dental hardware were reconstructed with standard filtered back-projection, linear interpolation metal artifact reduction (LIMAR), and iterative metal artifact reduction. The image quality of sections that contained metal was analyzed for the severity of artifacts and diagnostic value.A total of 455 sections (mean ± standard deviation, 9.1 ± 4.1 sections per patient) contained metal and were evaluated with each reconstruction method. Sections without metal were not affected by the algorithms and demonstrated image quality identical to each other. Of these sections, 38% were considered nondiagnostic with filtered back-projection, 31% with LIMAR, and only 7% with iterative metal artifact reduction. Thirty-three percent of the sections had poor image quality with filtered back-projection, 46% with LIMAR, and 10% with iterative metal artifact reduction. Thirteen percent of the sections with filtered back-projection, 17% with LIMAR, and 22% with iterative metal artifact reduction were of moderate image quality, 16% of the sections with filtered back-projection, 5% with LIMAR, and 30% with iterative metal artifact reduction were of good image quality, and 1% of the sections with LIMAR and 31% with iterative metal artifact reduction were of excellent image quality.Iterative metal artifact reduction yields the highest image quality in comparison with filtered back-projection and linear interpolation metal artifact reduction in patients with metal hardware in the head and neck area.
EVALuna2:14480

Individual Calculation of Effective Dose and Risk of Malignancy Based on Monte Carlo Simulations after Whole Body Computed Tomography - Kopp, Markus; Loewe, Tobias; Wüst, Wolfgang; Brand, Michael; Wetzl, Matthias; Nitsch, Wolfram; Schmidt, Daniela; Beck, Michael; Schmidt, Bernhard; Uder, Michael; May, Matthias (Scientific Reports, 2020)
Detailed knowledge about radiation exposure is crucial for radiology professionals. The conventional calculation of effective dose (ED) for computed tomography (CT) is based on dose length product (DLP) and population-based conversion factors (k). This is often imprecise and unable to consider individual patient characteristics. We sought to provide more precise and individual radiation exposure calculation using image based Monte Carlo simulations (MC) in a heterogeneous patient collective and to compare it to phantom based MC provided from the National Cancer Institute (NCI) as academic reference. Dose distributions were simulated for 22 patients after whole-body CT during Positron Emission Tomography-CT. Based on MC we calculated individual Lifetime Attributable Risk (LAR) and Excess Relative Risk (ERR) of cancer mortality. EDMC was compared to EDDLP and EDNCI. EDDLP (13.2 ± 4.5 mSv) was higher compared to EDNCI (9.8 ± 2.1 mSv) and EDMC (11.6 ± 1.5 mSv). Relative individual differences were up to −48% for EDMC and −44% for EDNCI compared to EDDLP. Matching pair analysis illustrates that young age and gender are affecting LAR and ERR significantly. Because of these uncertainties in radiation dose assessment automated individual dose and risk estimation would be desirable for dose monitoring in the future.
CRIS-Team Scopus Importer:2020-06-23

Influence of Cardiac MR Imaging on DNA Double-Strand Breaks in Human Blood Lymphocytes - Brand, Michael; Ellmann, Stephan; Sommer, Matthias; May, Matthias; Eller, Achim; Wüst, Wolfgang; Engert, Christina; Achenbach, Stephan; Kuefner, Michael A.; Bäuerle, Tobias; Lell, Michael; Uder, Michael (Radiology, 2015)
To evaluate the ability of magnetic resonance (MR) imaging to induce deoxyribonucleic acid (DNA) damage in patients who underwent cardiac MR imaging in daily routine by using ?-H2AX immunofluorescence microscopy.This study complies with the Declaration of Helsinki and was performed according to local ethics committee approval. Informed patient consent was obtained. Blood samples from 45 patients (13 women, 32 men; mean age, 50.3 years [age range, 20-89 years]) were obtained before and after contrast agent-enhanced cardiac MR imaging. MR imaging-induced double-strand breaks (DSBs) were quantified in isolated blood lymphocytes by using immunofluorescence microscopy after staining the phosphorylated histone variant ?-H2AX. Twenty-nine patients were examined with a myocarditis protocol (group A), 10 patients with a stress-testing protocol (group B), and six patients with flow measurements and angiography (group C). Paired t test was performed to compare excess foci before and after MR imaging.The mean baseline DSB level before MR imaging and 5 minutes after MR imaging was, respectively, 0.116 DSB per cell ± 0.019 (standard deviation) and 0.117 DSB per cell ± 0.019 (P = .71). There was also no significant difference in DSBs in these subgroups (group A: DSB per cell before and after MR imaging, respectively, 0.114 and 0.114, P = .91; group B: DSB per cell before and after MR imaging, respectively, 0.123 and 0.124, P = .78; group C: DSB per cell before and after MR imaging, respectively, 0.114 and 0.115, P = .36).By using ?-H2AX immunofluorescence microscopy, no DNA DSBs were detected after cardiac MR imaging.
EVALuna2:12028

Influence of Different Antioxidants on X-Ray Induced DNA Double-Strand Breaks (DSBs) Using ?-H2AX Immunofluorescence Microscopy in a Preliminary Study - Brand, Michael; Sommer, Matthias; Ellmann, Stephan; Wüst, Wolfgang; May, Matthias; Eller, Achim; Vogt, Sabine; Lell, Michael; Kuefner, Michael A.; Uder, Michael (PLoS ONE, 2015)
Radiation exposure occurs in X-ray guided interventional procedures or computed tomography (CT) and ?-H2AX-foci are recognized to represent DNA double-strand breaks (DSBs) as a biomarker for radiation induced damage. Antioxidants may reduce the induction of ?-H2AX-foci by binding free radicals. The aim of this study was to establish a dose-effect relationship and a time-effect relationship for the individual antioxidants on DSBs in human blood lymphocytes.Blood samples from volunteers were irradiated with 10 mGy before and after pre-incubation with different antioxidants (zinc, trolox, lipoic acid, ß-carotene, selenium, vitamin E, vitamin C, N-acetyl-L-cysteine (NAC) and Q 10). Thereby, different pre-incubation times, concentrations and combinations of drugs were evaluated. For assessment of DSBs, lymphocytes were stained against the phosphorylated histone variant ?-H2AX.For zinc, trolox and lipoic acid regardless of concentration or pre-incubation time, no significant decrease of ?-H2AX-foci was found. However, ß-carotene (15%), selenium (14%), vitamin E (12%), vitamin C (25%), NAC (43%) and Q 10 (18%) led to a significant reduction of ?-H2AX-foci at a pre-incubation time of 1 hour. The combination of different antioxidants did not have an additive effect.Antioxidants administered prior to irradiation demonstrated the potential to reduce ?-H2AX-foci in blood lymphocytes.
EVALuna2:14494

Influence of risk-organ-based tube current modulation on CT-induced DNA double-strand breaks in a biological phantom model - Brand, Michael; Wüst, Wolfgang; May, Matthias; Uder, Michael; Sommer, Matthias (Journal of Radiation Research, 2018)
Techniques for dose reduction in computed tomography (CT) are receiving increasing attention. Lowering the tube current in front of the patient, known as risk-organ-based tube current modulation (RTM), represents a new approach. Physical dose parameters can determine the exposure but are not able to assess the biological-X-ray interactions. The purpose of this study was to establish a biological phantom model to evaluate the effect of RTM on X-ray-induced DNA double-strand breaks (DSBs). In breast phantoms and in the location of the spine in an Alderson phantom, isolated human blood lymphocytes were irradiated using a 128-slice CT scanner. A standard thoracic CT protocol (120 kV, 110 ref. mAs, anatomy-based tube current modulation, pitch 0.6, scan length 30 cm) with and without RTM was used. X-ray-induced DSBs were quantified in isolated blood lymphocytes using immunofluorescence microscopy after staining for the phosphorylated histone variant γ-H2AX. Using RTM, the resulting DNA damage reduction was 41% in superficial breast locations (P = 0.0001), 28% in middle breast locations (P = 0.0003) and 29% in lower breast locations (P = 0.0001), but we found a DNA damage increase of 36% in superficial spine locations (P = 0.0001) and of 26% in deep spine locations (P = 0.0001). In summary, we established a biological phantom model that is suitable for detecting DNA damage in distinct organs. In addition, we were able to show that, using RTM, X-ray-induced DNA damage in the breast can be significantly reduced; however, there is a significant increase in DSBs in the location of the spine.
EVALuna2:36108

Local control of perivascular malignant liver lesions using percutaneous irreversible electroporation: initial experiences - Eller, Achim; Schmid, Andrea; Schmidt, Joachim; May, Matthias; Brand, Michael; Saake, Marc; Uder, Michael; Lell, Michael (Cardiovascular and Interventional Radiology, 2015)
This study was designed to assess efficacy and safety in the treatment of perivascular malignant liver lesions using percutaneous, computed tomography (CT)-guided irreversible electroporation (IRE).Fourteen patients (mean age 58 ± 11 years) with 18 malignant liver lesions were consecutively enrolled in this study. IRE was performed in patients not eligible for surgery and lesions abutting large vessels or bile ducts. Follow-up exams were performed using multislice-CT (MS-CT) or MRI.Medium lesion diameter was 20 ± 5 mm. Ten of 14 (71 %) were successfully treated with no local recurrence to date (mean follow-up 388 ± 160 days). One case left initial tumor control unclear and additional RFA was performed 4 weeks after IRE. Complications occurred in 4 of 14 (29 %) cases. In one case, intervention was terminated and abdominal bleeding required laparotomy. In two cases, a postinterventional hematothorax required intervention. In another case, abdominal bleeding could be managed conservatively. No complications related to the bile ducts occurred.Percutaneous IRE seems to be effective in perivascular lesions but is associated with a higher complication rate compared with thermoablative techniques.
EVALuna2:14379

Low-Dose CT of the Paranasal Sinuses: Minimizing X-Ray Exposure with Spectral Shaping - Wüst, Wolfgang; May, Matthias; Saake, Marc; Brand, Michael; Uder, Michael; Lell, Michael (European Radiology, 2016)
Shaping the energy spectrum of the X-ray beam has been shown to be beneficial in low-dose CT. This study's aim was to investigate dose and image quality of tin filtration at 100 kV for pre-operative planning in low-dose paranasal CT imaging in a large patient cohort.In a prospective trial, 129 patients were included. 64 patients were randomly assigned to the study protocol (100 kV with additional tin filtration, 150mAs, 192x0.6-mm slice collimation) and 65 patients to the standard low-dose protocol (100 kV, 50mAs, 128 × 0.6-mm slice collimation). To assess the image quality, subjective parameters were evaluated using a five-point scale. This scale was applied on overall image quality and contour delineation of critical anatomical structures.All scans were of diagnostic image quality. Bony structures were of good diagnostic image quality in both groups, soft tissues were of sufficient diagnostic image quality in the study group because of a high level of noise. Radiation exposure was very low in both groups, but significantly lower in the study group (CTDIvol 1.2 mGy vs. 4.4 mGy, p < 0.001).Spectral optimization (tin filtration at 100 kV) allows for visualization of the paranasal sinus with sufficient image quality at a very low radiation exposure.o Spectral optimization (tin filtration) is beneficial to low-dose parasinus CT o Tin filtration at 100 kV yields sufficient image quality for pre-operative planning o Diagnostic parasinus CT can be performed with an effective dose <0.05 mSv.
EVALuna2:14599

Potential Limitations of Established Blood-Dosimetry Models for Lu-177 Therapy - Ritt, Philipp; Jobic, C.; Grings, Andreas; Beck, Michael; Schmidkonz, Christian; Kuwert, Torsten; Uder, Michael; Brand, Michael (EUROPEAN JOURNAL OF NUCLEAR MEDICINE AND MOLECULAR IMAGING, 2021)
CRIS-Team WoS Importer:2022-01-07

Prospectively ECG-triggered high-pitch coronary angiography with third-generation dual-source CT at 70 kVp tube voltage: Feasibility, image quality, radiation dose, and effect of iterative reconstruction - Hell, Michaela M.; Bittner, Daniel; Schuhbaeck, Annika; Muschiol, Gerd; Brand, Michael; Lell, Michael; Uder, Michael; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
Low tube voltage reduces radiation exposure in coronary CT angiography (CTA). Using 70 kVp tube potential has so far not been possible because CT systems were unable to provide sufficiently high tube current with low voltage.We evaluated feasibility, image quality (IQ), and radiation dose of coronary CTA using a third-generation dual-source CT system capable of producing 450 mAs tube current at 70 kVp tube voltage.Coronary CTA was performed in 26 consecutive patients with suspected coronary artery disease, selected for body weight <100 kg and heart rate <60 beats/min. High-pitch spiral acquisition was used. Filtered back projection (FBP) and iterative reconstruction (IR) algorithms were applied. IQ was assessed using a 4-point rating scale (1 = excellent, 4 = nondiagnostic) and objective parameters.Mean age was 62 ± 9 years (46% males; mean body mass index, 27.7 ± 3.8 kg/m(2); mean heart rate, 54 ± 5 beats/min). Mean dose-length product was 20.6 ± 1.9 mGy × cm; mean estimated effective radiation dose was 0.3 ± 0.03 mSv. Diagnostic IQ was found in 365 of 367 (FBP) and 366 of 367 (IR) segments (P nonsignificant). IQ was rated "excellent" in 53% (FBP) and 86% (IR) segments (P = .001) and "nondiagnostic" in 2 (FBP) and 1 segment (IR) (P nonsignificant). Mean IQ score was lesser in FBP vs IR (1.5 ± 0.4 vs 1.1 ± 0.2; P < .001). Image noise was lower in IR vs FBP (60 ± 10 HU vs 74 ± 8 HU; P < .001).In patients <100 kg and with a regular heart rate <60 beats/min, third-generation dual-source CT using high-pitch spiral acquisition and 70 kVp tube voltage is feasible and provides both robust IQ and very low radiation exposure.
EVALuna2:11954

Radiation dose reduction in parasinus CT by spectral shaping - May, Matthias; Brand, Michael; Lell, Michael; Sedlmair, Martin; Allmendinger, Thomas; Uder, Michael; Wüst, Wolfgang (Neuroradiology, 2017)
Spectral shaping aims to narrow the X-ray spectrum of clinical CT. The aim of this study was to determine the image quality and the extent of radiation dose reduction that can be achieved by tin prefiltration for parasinus CT.All scans were performed with a third generation dual-source CT scanner. A study protocol was designed using 100 kV tube voltage with tin prefiltration (200 mAs) that provides image noise levels comparable to a low-dose reference protocol using 100 kV without spectral shaping (25 mAs). One hundred consecutive patients were prospectively enrolled and randomly assigned to the study or control group. All patients signed written informed consent. The study protocol was approved by the local Institutional Review Board and applies to the HIPAA. Subjective and objective image quality (attenuation values, image noise, and contrast-to-noise ratio (CNR)) were assessed. Radiation exposure was assessed as volumetric CT dose index, and effective dose was estimated. Mann-Whitney U test was performed for radiation exposure and for image noise comparison.All scans were of diagnostic image quality. Image noise in air, in the retrobulbar fat, and in the eye globe was comparable between both groups (all p > 0.05). CNReye globe/air did not differ significantly between both groups (p = 0.7). Radiation exposure (1.7 vs. 2.1 mGy, p < 0.01) and effective dose (0.055 vs. 0.066 mSv, p < 0.01) were significantly reduced in the study group.Radiation dose can be further reduced by 17% for low-dose parasinus CT by tin prefiltration maintaining diagnostic image quality.
EVALuna2:14651

Radiation Induced DNA Double-Strand Breaks in Radiology - Kuefner, M. A.; Brand, Michael; Engert, C.; Schwab, S. A.; Uder, Michael (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Shortly after the discovery of X-rays, their damaging effect on biological tissues was observed. The determination of radiation exposure in diagnostic and interventional radiology is usually based on physical measurements or mathematical algorithms with standardized dose simulations. ?-H2AX immunofluorescence microscopy is a reliable and sensitive method for the quantification of radiation induced DNA double-strand breaks (DSB) in blood lymphocytes. The detectable amount of these DNA damages correlates well with the dose received. However, the biological radiation damage depends not only on dose but also on other individual factors like radiation sensitivity and DNA repair capacity. Iodinated contrast agents can enhance the x-ray induced DNA damage level. After their induction DSB are quickly repaired. A protective effect of antioxidants has been postulated in experimental studies. This review explains the prinicple of the ?-H2AX technique and provides an overview on studies evaluating DSB in radiologic examinations.Radiologic examinations including CT and angiography induce DNA double-strand breaks. Even after mammography a slight but significant increase is detectable in peripheral blood lymphocytes. The number of radiation induced double-strand breaks correlates well with the radiation dose. Individual factors including radiation sensitivity, DNA repair capacity and the application of iodinated contrast media has an influence on the DNA damage level.
EVALuna2:14515

Reduction of X-ray-induced DNA damage in normal human cells treated with the PrC-210 radioprotector - Brand, Michael; Sommer, Matthias; Jermusek, Frank; Fahl, William E.; Uder, Michael (Biology Open, 2018)
The aim of our study was to determine the protective efficacy of the PrC-210 aminothiol radioprotector against X-ray-induced DNA damage in normal human cells and to establish dose- and time-effect models for future PrC-210 use in humans. The PrC-210 structure has a branched structure which enables scavenging of reactive oxygen species (ROS) away from DNA. Normal human blood lymphocytes, fibroblasts and naked genomic DNA were exposed to PrC-210 seconds to hours prior to irradiation. Biological (γ-H2AX foci), chemical (8-oxo-deoxyguanosine) and physical (genomic DNA electrophoretic migration) DNA damage endpoints were scored to determine the ability of PrC-210 to suppress radiation-induced DNA damage. X-ray-induced γ-H2AX foci in blood lymphocytes were reduced by 80% after irradiation with 10, 50 and 100 mGy, and DNA double-strand breaks in fibroblasts were reduced by 60% after irradiation with 20 Gy. Additionally, we observed a reduction of 8-oxo-deoxyguanosine (an ROS-mediated, DNA damage marker) in human genomic DNA to background in a PrC-210 dose-dependent manner. PrC-210 also eliminated radiation-induced cell death in colony formation assays after irradiation with 1 Gy. The protective efficacy of PrC-210 in each of these assay systems supports its development as a radioprotector for humans in multiple radiation exposure settings.
EVALuna2:36109

Research in radiology - Semelka, Richard C.; Brand, Michael; Uder, Michael; Kuefner, Michael A.; Stonestreet, John; Elias, Jorge (Wiley Blackwell, 2013)
CRIS-Team Scopus Importer:2023-03-08

Significant Suppression of CT Radiation-Induced DNA Damage in Normal Human Cells by the PrC-210 Radioprotector - Jermusek, Frank; Benedict, Chelsea; Dreischmeier, Emma; Brand, Michael; Uder, Michael; Jeffery, Justin J.; Ranallo, Frank N.; Fahl, William E. (Radiation Research, 2018)
While computed tomography (CT) is now commonly used and considered to be clinically valuable, significant DNA double-strand breaks (γ-H2AX foci) in white blood cells from adult and pediatric CT patients have been frequently reported. In this study to determine whether γ-H2AX foci and X-ray-induced naked DNA damage are suppressed by administration of the PrC-210 radioprotector, human blood samples were irradiated in a CT scanner at 50-150 mGy with or without PrC-210, and γ-H2AX foci were scored. X-ray-induced naked DNA damage was also studied, and the DNA protective efficacy of PrC-210 was compared against 12 other common "antioxidants." PrC-210 reduced CT radiation-induced γ-H2AX foci in white blood cells to near background ( P < 0.0001) at radiation doses of 50-150 mGy. PrC-210 was most effective among the 13 "antioxidants" in reducing naked DNA X-ray damage, and its addition at 30 s before an •OH pulse reduced to background the •OH insult that otherwise induced >95% DNA damage. A systemic PrC-210 dose known to confer 100% survival in irradiated mice had no discernible effect on micro-CT image signal-to-noise ratio and CT image integrity. PrC-210 suppressed DNA damage to background or near background in each of these assay systems, thus supporting its development as a radioprotector for humans in multiple radiation exposure settings.
EVALuna2:34691

The effect of calyculin A on the dephosphorylation of the histone γ-H2AX after formation of X-ray-induced DNA double-strand breaks in human blood lymphocytes - Kuefner, Michael A.; Brand, Michael; Engert, Christina; Kappey, Hanna; Uder, Michael; Distel, Luitpold (International Journal of Radiation Biology, 2013)
Purpose: The purpose of this study was to investigate the effect of calyculin A on the number of γ-H2AX foci (phosphorylated histone variant 2AX) in lymphocytes after in vitro and in vivo irradiation with rather low doses as they are used in diagnostic and interventional radiology. Materials and methods: For in vitro experiments blood samples of 14 healthy volunteers were irradiated with different doses (10, 50, 100 mGy) and incubated with (0.01, 0.1, 1, 10 nM) or without calyculin A for up to 2 hours. Non-irradiated samples with and without calyculin A served as controls. For in vivo evaluation blood samples were collected from seven patients undergoing computed tomography (CT) both with 1 nM calyculin A containing vials and vials without calyculin A. Foci were quantified in isolated lymphocytes using γ-H2AX immunofluorescence microscopy. Results: 1 nM calyculin A led to a complete inhibition of γ-H2AX foci loss in irradiated samples whereas no inhibition of p53 binding protein 1 (53 BP1) foci was found. Lower concentrations of the phosphatase inhibitor did not have a sufficient effect on foci decrease. Calyculin A did not affect foci levels in non-irradiated samples. If no calyculin A was added into the vial before the blood draws detectable CT-induced foci levels were lower in all patients with a reduction of the medians of 35%. Conclusions: Using γ-H2AX immunofluorescence microscopy calyculin A can be a useful tool to mark the induced γ-H2AX foci after low dose irradiation and to avoid an underestimation of the real deoxyribonucleic acid (DNA) damage in in vitro and in vivo experiments. © 2013 Informa UK, Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: γ-H2AX; Calyculin A; DNA double-strand break repair

Ultra-low dose comprehensive cardiac CT imaging in a patient with acute myocarditis - Tröbs, Monique; Brand, Michael; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
The ability of contrast-enhanced CT to detect "late enhancement" in a fashion similar to magnetic resonance imaging has been previously reported. We report a case of acute myocarditis with coronary CT angiography as well as "late enhancement" imaging with ultra-low effective radiation dose.
EVALuna2:11957

X-Ray Induced Formation of γ-H2AX Foci after Full-Field Digital Mammography and Digital Breast-Tomosynthesis - Schwab, Siegfried; Brand, Michael; Schlude, Ina-Kristin; Wüst, Wolfgang; Meier-Meitinger, Martina; Distel, Luitpold; Schulz-Wendtland, Rüdiger; Uder, Michael; Uder, Michael; Kuefner, Michael A. (PLoS ONE, 2013)
Purpose:To determine in-vivo formation of x-ray induced γ-H2AX foci in systemic blood lymphocytes of patients undergoing full-field digital mammography (FFDM) and to estimate foci after FFDM and digital breast-tomosynthesis (DBT) using a biological phantom model.Materials and Methods:The study complies with the Declaration of Helsinki and was performed following approval by the ethic committee of the University of Erlangen-Nuremberg. Written informed consent was obtained from every patient. For in-vivo tests, systemic blood lymphocytes were obtained from 20 patients before and after FFDM. In order to compare in-vivo post-exposure with pre-exposure foci levels, the Wilcoxon matched pairs test was used. For in-vitro experiments, isolated blood lymphocytes from healthy volunteers were irradiated at skin and glandular level of a porcine breast using FFDM and DBT. Cells were stained against the phosphorylated histone variant γ-H2AX, and foci representing distinct DNA damages were quantified.Results:Median in-vivo foci level/cell was 0.086 (range 0.067-0.116) before and 0.094 (0.076-0.126) after FFDM (p = 0.0004). In the in-vitro model, the median x-ray induced foci level/cell after FFDM was 0.120 (range 0.086-0.140) at skin level and 0.035 (range 0.030-0.050) at glandular level. After DBT, the median x-ray induced foci level/cell was 0.061 (range 0.040-0.081) at skin level and 0.015 (range 0.006-0.020) at glandular level.Conclusion:In patients, mammography induces a slight but significant increase of γ-H2AX foci in systemic blood lymphocytes. The introduced biological phantom model is suitable for the estimation of x-ray induced DNA damages in breast tissue in different breast imaging techniques. © 2013 Schwab et al.
CRIS-Team Scopus Importer:2023-03-08